Strategi Komunikasi Dan Informatika Dalam Meningkatkan Kebutuhan Masyarakat Terhadap Berita Melalui Aplikasi Simata Sumsel - Cahaya, Anggi; Nuraida; Yahya, Ahmad Harun (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
The background is a comprehensive application which summarizes various information and data such as the efforts made by the South Sumatra Provincial Government for regional and community progress, population and employment, agriculture, plantations, population, as well as detailed information regarding the condition of South Sumatra. So this research analyzes "Communication and Informatics Strategies in Increasing People's Needs for News Through the South Sumatra Simata Application. With the aim of the research to find out communication and informatics strategies in increasing the public's need for news through the Simata Sumsel application. The research methodology uses qualitative. Data collection techniques include observation, editing and documentation. The results of the research are a comprehensive application which summarizes various information and data such as the efforts that have been made by the South Sumatra Provincial Government for the progress of the region and society, the population and all the prospective needs of the community to detailed information regarding the condition of South Sumatra from the sub-district to district and city levels at this time. "technology has become a necessity," it is time for technological transformation to be necessary, for this reason we created SIMATA to make it easier for local communities to access various data and information related to social, economic, political, geographical and other conditions.